2015
DOI: 10.1017/s1368980015000567
|View full text |Cite
|
Sign up to set email alerts
|

Red and processed meat consumption and purchasing behaviours and attitudes: impacts for human health, animal welfare and environmental sustainability

Abstract: Objective: Higher intakes of red and processed meat are associated with poorer health outcomes and negative environmental impacts. Drawing upon a population survey the present paper investigates meat consumption behaviours, exploring perceived impacts for human health, animal welfare and the environment. Design: Structured self-completion postal survey relating to red and processed meat, capturing data on attitudes, sustainable meat purchasing behaviour, red and processed meat intake, plus sociodemographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 46 publications
11
98
4
3
Order By: Relevance
“…Nonetheless, in order to improve citizens' and the planet's health, it has been argued that it is relevant to promote sustainable diets through national guidelines, which would require changes in policy frameworks regarding food production and On the other hand, some barriers to meat consumption reduction were also identified. Even though there is clear evidence of the environmental footprint and health impacts of animal-based diets [7,62] in Colombia, reducing meat consumption could face other obstacles that should be taken into account, such as the availability of the products that could substitute meat. While Colombia is self-sufficient in terms of fruits, roots, tubers, sugar, meat, and animal products, the country depends on the imports of legumes, such as lentils and chickpeas [29].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in order to improve citizens' and the planet's health, it has been argued that it is relevant to promote sustainable diets through national guidelines, which would require changes in policy frameworks regarding food production and On the other hand, some barriers to meat consumption reduction were also identified. Even though there is clear evidence of the environmental footprint and health impacts of animal-based diets [7,62] in Colombia, reducing meat consumption could face other obstacles that should be taken into account, such as the availability of the products that could substitute meat. While Colombia is self-sufficient in terms of fruits, roots, tubers, sugar, meat, and animal products, the country depends on the imports of legumes, such as lentils and chickpeas [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study realized in Europe showed that consumers give high importance to environmental and animal welfare issues but there is often a gap between attitudes and behavior (Verbeke et al, 2010). On the other hand, a more powerful reason for the change of habits in meat consumption is the concern about safety and health (Clonan et al, 2015).…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…One study of adults from 842 households in Nottinghamshire (UK) (Clonan et al 2012) found that consumers gave 'health' reasons more frequently than 'sustainably sourced' for purchasing fish, although the respondents did not meet the recommended intake of fish set by the Department of Health. A similar conflict was identified in a subsequent paper on meat, whereby consumers were more likely to be motivated by 'health' and 'animal welfare issues' for avoiding red and processed meat than 'environmental sustainability' (Clonan et al 2015). A study conducted by the Eating Better Alliance explored public awareness of the environmental impact of food and their willingness to reduce meat consumption, and identified opportunities to shift towards a more sustainable diet (Dibb & Fitzpatrick 2014).…”
Section: Sustainable Food Choicesa Quandary For Consumers?mentioning
confidence: 80%
“…A similar conflict was identified in a subsequent paper on meat, whereby consumers were more likely to be motivated by ‘health’ and ‘animal welfare issues’ for avoiding red and processed meat than ‘environmental sustainability’ (Clonan et al . ). A study conducted by the Eating Better Alliance explored public awareness of the environmental impact of food and their willingness to reduce meat consumption, and identified opportunities to shift towards a more sustainable diet (Dibb & Fitzpatrick ).…”
Section: Sustainable Food Choices – a Quandary For Consumers?mentioning
confidence: 97%